Development of Herbarium Media In The Course Plant Taxonomy Course Low UIN Mataram - Hidiyatul Fithi; Ervina Titi Jayanti; Firman Ali Rahman (Institute of Educational, Research, and Community Service, 2023)
This study aims to develop a product in the form of a herbarium collection of ferns that can be used as a learning medium both theoretically and practically in the subject of lower plant taxonomy at UIN Mataram. This research is a development research that refers to the Borg and Gall model. The sample used was fourth semester students taken by random sampling. The data obtained were analyzed by descriptive qualitative and descriptive quantitative. The herbarium book media was validated by media experts with the results of product validation test data analysis obtained a percentage of 84% with valid criteria. After making improvements according to the suggestions from the validator, then continued with small-scale product trials with a percentage value of 85% which showed that the fern herbarium book media was valid and well used in learning, especially in low-level plant taxonomy courses on Pteridophyta material